2012
DOI: 10.1111/j.1365-2966.2012.21785.x
|View full text |Cite
|
Sign up to set email alerts
|

Probing the origin of giant radio haloes through radio and γ-ray data: the case of the Coma cluster

Abstract: We combine for the first time all available information about the spectral shape and morphology of the radio halo of the Coma cluster with the recent γ -ray upper limits obtained by the Fermi-Large Area Telescope (LAT) and with the magnetic field strength derived from Faraday rotation measures. We explore the possibility that the radio emission is due to synchrotron emission of secondary electrons. First, we investigate the case of pure secondary models that are merely based on the mechanism of continuous inje… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
138
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(152 citation statements)
references
References 92 publications
14
138
0
Order By: Relevance
“…Our results indicate that the CR protons accelerated at shocks in the cluster outskirts may be capable of producing secondary electrons with the right energy spectral slope (q ss e ≈ 5.25-5.5) for the spectral index of observed radio halos. Brunetti et al (2012), however, argued that at least for the Coma cluster, the hadronic model that requires the CR proton energy 3%-5% of the thermal energy may violate the γ -ray upper limit set by Fermi-LAT observations, provided that the magnetic field is not much stronger than that measured/constrained by Faraday RM. Moreover, according to a more recent Fermi-LAT paper (Ackermann et al 2013), this limit has become even more stringent, constraining the CR proton energy down to 1% of the thermal energy in clusters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results indicate that the CR protons accelerated at shocks in the cluster outskirts may be capable of producing secondary electrons with the right energy spectral slope (q ss e ≈ 5.25-5.5) for the spectral index of observed radio halos. Brunetti et al (2012), however, argued that at least for the Coma cluster, the hadronic model that requires the CR proton energy 3%-5% of the thermal energy may violate the γ -ray upper limit set by Fermi-LAT observations, provided that the magnetic field is not much stronger than that measured/constrained by Faraday RM. Moreover, according to a more recent Fermi-LAT paper (Ackermann et al 2013), this limit has become even more stringent, constraining the CR proton energy down to 1% of the thermal energy in clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Vazza et al (2012) also showed that the CR pressure distribution could be temporarily inverted, that is, the CR pressure can increase outward. Brunetti et al (2012), on the other hand, attempted to constrain the radial distributions of nonthermal components (including the CR proton energy density) in the Coma cluster by combining radio observations with recent Fermi-LAT γ -ray observations and with Faraday rotation measure (RM) data. They argued that the model based on the turbulent acceleration of secondary electrons would best reproduce the radio halo of the Coma cluster with the CR energy density that scales with the thermal energy density as ε CR ∝ ε θ th with θ ≈ −0.1 to −0.35, implying that ε CR is higher at lower ε th .…”
mentioning
confidence: 99%
“…In the turbulent re-acceleration model, electrons are re-accelerated by merger induced magnetohydrodynamical turbulence (e.g., Schlickeiser et al 1987;Brunetti et al 2001;Petrosian 2001;Pinzke et al 2015). Secondary models are challenged by the large energy content of cosmic ray protons needed to explain radio halos with very steep spectra (Brunetti 2004;Brunetti et al 2008) and by the non-detection of γ-rays (e.g., Jeltema & Profumo 2011;Brunetti et al 2012;Ackermann et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In an alternative model, radio halos are produced by secondary electrons injected during proton-proton collisions in the ICM (e.g., Dennison 1980;Blasi & Colafrancesco 1999;Dolag & Enßlin 2000;Miniati et al 2001;Keshet & Loeb 2010). Secondary models are challenged by the large energy content of cosmic ray protons needed to explain radio halos with very steep spectra (e.g., Brunetti et al 2008) and by the non-detection of γ-rays from radio halos (e.g., Jeltema & Profumo 2011;Brunetti et al 2012). …”
Section: Introductionmentioning
confidence: 99%